1981
DOI: 10.1007/bf00121380
|View full text |Cite
|
Sign up to set email alerts
|

The albedo of snow for partially cloudy skies

Abstract: The albedo of snow for different cloudiness conditions is an important parameter in the Earth's radiation budget analysis and in the study of snowpack thermal conditions. An efficient method is presented for approximate calculation of incident spectral solar flux and snowcover albedo in terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 29 publications
2
17
1
Order By: Relevance
“…Owing to the selective absorption in the near infra-red, the LI-COR pyranometer could possibly overestimate the reflected radiation. Albedos calculated in this study are substantially lower than those postulated by Sellers (1 969, or the values reported by Choudhury (198 l), Choudhury and Chang (1981a, 1981b and Warren (1982). This has the effect of significantly increasing the net solar radiation, even after new snow has fallen.…”
Section: Radiation Measurementcontrasting
confidence: 77%
“…Owing to the selective absorption in the near infra-red, the LI-COR pyranometer could possibly overestimate the reflected radiation. Albedos calculated in this study are substantially lower than those postulated by Sellers (1 969, or the values reported by Choudhury (198 l), Choudhury and Chang (1981a, 1981b and Warren (1982). This has the effect of significantly increasing the net solar radiation, even after new snow has fallen.…”
Section: Radiation Measurementcontrasting
confidence: 77%
“…But, as snow ages and the number of melt/freeze events to which it is subjected increases, the specular reflection component increases especially in the forward direction. Furthermore, the specular reflection component increases with solar zenith angle (SZA) [Salomonson and Marlatt, 1968;Choudhury and Chang, 1981;Dozier et al, 1981]. As noted by Steffen [1987], fresh snow with a grain radius of 0.15 mm is nearly a Lambertian (isotropic) target, but the anisotropic nature of snow reflectance increases with increasing grain size.…”
Section: Albedo Of Snowmentioning
confidence: 98%
“…In addition to the natural variability of snow albedo due to metamorphosis, there is evidence that carbon from industrial pollution or soot, produced in nonpolar areas, may cause a reduction in the albedo of fresh snow and thus increase the amount of solar radiation that is absorbed at the surface [Chylek et al, 1983;Warren andWiscombe, 1980, 1985]. The magnitude of decrease in snow albedo caused by soot may be equal to that of the atmospheric effects of Arctic haze, in which less shortwave radiation is absorbed at the surface because of the haze [Clarke and Noone, 1985].…”
Section: Albedo Of Snowmentioning
confidence: 99%
“…Thus, clouds as well as snow-ice surfaces absorb selectively in the near-infrared. This implies that the integrated surface albedo under overcast conditions exceeds the clear-sky value (Grenfell and Maykut 1977;Grenfell and Perovich 1984;Choudhury and Chang 1981;Shine and Henderson-Sellers 1985). The importance of the surface is underscored by recent observational findings indicating that interannual variations of snow cover are, to a large extent, responsible for the interannual variability of surface air temperature over northern land areas, especially during spring (Groisman et al 1994).…”
Section: Nsa-aao Primary Scientific Focus: Highlatitude Phenomenamentioning
confidence: 99%